Field calculation in models of man in the near-field of antennas - Schaller, G; Engelbrecht, Rainer; Erb, J (IEEE, 1995)
For two examples the electromagnetic field is calculated inside and in the vicinity of properly modelled man in the near-field of antennas. The first example illustrates the SAR-distribution in a medical attendant near a deep hyperthermia system, whereas in the second example fields are calculated in a human head exposed to hand-held E-net phones. Both cases are investigated applying a 3-D field calculation program based on a finite integration algorithm.
lhft_intern.bib::thirty_years_LHFT_353